Kebudayaan dan Agama Jawa dalam Perspektif Clifford Geertz - Nasruddin Nasruddin (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2011)
Talking about Javanese culture, anthropologist will often refer to Geertz’s thesis of santri-abangan-priyayi. Geertz’s book, Religion of Java, has been a “holy book” for those who concerns for observing and researching Javanese culture and society. In this context, Geertz has acknowledged a theory of social system of Javanese people. In his another book, Interpretation of Culture, Geertz identifies culture based on the last-concept of Kluckholn. He sets culture as a text which has to be meaningfully interpreted, not only as a concrete manner. In addition, he sets religion as cultural values within is embodied within the meanings. Everyone can interpret and experience those meanings in his own approach. Since Geertz conducted a study on The Religion of Java, the study continues, either agree or disagree with him. This article deliberately take the starting point of Geertz’s studies related to the concept of trichotomies; students, abangan and priyanyi. Although this has led to the concept of trichotomies to pros and cons among scientists, but the thing that needs to be underlined is that Geertz's conception of Islam of Java are a source of inspiration for the study of Islam in Indonesia. In addition, this article not only discusses about Geertz’s concept of religion, but also the concept of Islamic Religion in Indonesia.